Matabolomic Changes Induced by 6-Benzylaminopurine in Polygonatum cyrtonema - Xincheng Liu; Huidong Yang; Bin Guo; Zhongdong Hu (Horticulturae, 2024)
Polygonatum cyrtonema Hua (family Asparagaceae) is an endemic plant in China that is valuable for its edible and medicinal uses. Plant growth regulators (PGRs) are natural or synthetic compounds that can regulate plant development and metabolism effectively. To explore potential applications of PGRs for improving the yield and bioactivity of this plant, four PGRs, including gibberellic acid (GA3), 6-benzylaminopurine (6-BA), naphthaleneacetic acid (NAA) and 24-epibrassinolide (EBL), were used in this study and sprayed on the growing seedlings of P. cyrtonema. All of these PGRs did not significantly affect the growth rate of P. cyrtonema, but they had varying effects on the polysaccharide and saponin content in the rhizome. NAA and 6-BA positively affected the polysaccharide content, while most PGR treatments negatively affected the saponin content. Widely targeted metabolomic analysis based on UPLC-MS/MS was conducted and revealed 101 differential metabolites in response to 6-BA, most of which were flavonoids, steroids and lipids. Most of the significantly changed flavonoids decreased under the 6-BA treatment. The study provides insights into the potential use of PGRs for improving the quality of P. cyrtonema, particularly in regulating the content of bioactive compounds.